Enhancing Festival Event Quality Through Trend-Driven Innovation in Regional Indonesia - Pratama, Handika Fikri; Yahyaddin, Muh; Iqbal, Muhmmad; Kurniawan, Ahmad; Fadhela, Rahmi; Wibowo, Budi; Hazisma, Suhairi (Politeknik Negeri Bandung, 2025)
This study investigates the stagnation in the conceptual execution of the Sagarurung Festival in the PALI Regency (Penukal Abab Lematang Ilir), which has remained largely unchanged over time and failed to incorporate contemporary trends and innovations. This lack of novelty has reduced visitor engagement, particularly among the younger demographic. To address this, the research explores how trend-driven innovation, operationalized through four core variables: strong festival atmosphere, harmonious interpersonal interaction, distinct cultural symbols, and rich festival activities, can enhance the attractiveness and quality of regional festivals. A quantitative approach using Structural Equation Modeling (SEM) was employed, with data collected from 285 festival attendees. The analysis revealed a statistically significant influence of a strong festival atmosphere on the three other variables. These findings support the development of a comprehensive event model that integrates emerging trends into local cultural contexts to revitalize festival experiences. Theoretically, this study extends event management literature by introducing trend-driven innovation as a strategic framework for enhancing the relevance and competitiveness of regional festivals. It offers a scalable model that can inform policy and practice in similar socio-cultural settings, contributing to increased tourism and sustained cultural preservation.